Anosognosia in Amnestic Mild Cognitive Impairment Is Related to Diminished Hippocampal Volume Comparable to Alzheimer’s Disease Dementia: Preliminary MRI Findings - Flores-Vázquez, Juan Francisco; Ramírez-García, Gabriel; Marrufo-Meléndez, Oscar René; Alcalá-Lozano, Ruth; Lietz, Morten Peter; Rodríguez-Agudelo, Yaneth; Acosta-Castillo, Gilberto Isaac; Renken, Remco J.; Aleman, Andre; Enriquez-Geppert, Stefanie; Sosa-Ortiz, Ana Luisa (Frontiers in Aging Neuroscience, 2021)
Although the presence of anosognosia in amnestic mild cognitive impairment (aMCI) may be predictive of conversion to Alzheimer’s disease (AD), little is known about its neural correlates in AD and aMCI. Four different groups were compared using volumetric and diffusion magnetic resonance imaging metrics in regions of interest (hippocampus and cingulum cortex gray matter, cingulum bundle white matter): aMCI subjects with anosognosia (n=6), aMCI subjects without anosognosia (n=12), AD subjects with anosognosia (n=6), and AD subjects without anosognosia (n=9). aMCI subjects with anosognosia displayed a significantly lower gray matter density (GMD) in the bilateral hippocampus than aMCI subjects without anosognosia, which was accounted for by bilateral hippocampal differences. Furthermore, we identified that the mean hippocampal gray matter density of aMCI subjects with anosognosia was not statistically different than that of AD subjects. The groups of aMCI and AD subjects with anosognosia also displayed a lower GMD in the bilateral cingulum cortex compared to subjects without anosognosia, but these differences were not statistically significant. No statistically significant differences were found in the fractional anisotropy or mean diffusivity of the hippocampus or cingulum between subjects with and without anosognosia in aMCI or AD groups. While these findings are derived from a small population of subjects and are in need of replication, they suggest that anosognosia in aMCI might be a useful clinical marker to suspect brain changes associated with AD neuropathology.